The Influence of Total Asset Turnover, Current Ratio, Profit Growth, and Company Size on Stock Returns in Food and Beverage Companies Listed on the IDX for the Period 2019-2023 - Apri Yanti Tambunan; Nia Novilana Sihombing; Petrisia Angelina Gultom; Daniel Edward Saragih; Wiliam, Wiliam (International Journal of Economics, Business and Innovation Research, 2025)
This study seeks to examine the impact of total asset turnover (TATO), current ratio (CR), profit growth, and business size on stock returns in food and beverage manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The research adopts a quantitative methodology, including multiple linear regression analysis. We acquired data from the annual financial statements of the enterprises that constituted the study's samples. The findings indicated that the Total Asset Turnover (TATO) and Current Ratio (CR) factors had a significant and beneficial influence on stock returns. The profit growth variable exerts a positive and significant influence on stock returns, however the firm size variable does not demonstrate a meaningful impact on stock returns. This study concludes that the company's financial performance, particularly regarding asset utilization efficiency and liquidity capacity, significantly influences stock returns in the food and beverage manufacturing sector.